Impact of organisational practices and language on an international business cooperation : the case of a German-Slovakian corporation - Schröder, Christin Irma (2015)
In the course of the EU integration process, Slovakia became a target of choice for German investors. The percentage of German foreign direct investment has increased sharply since 1995. A growing number of German small to medium sized enterprises discover Slovakia as profitable location for outsourcing and offshoring. However, little is known about German-Slovakian corporations and expatriate management in Slovakia. The aim of the study is to get an understanding of the impact of organisational culture and language on one specific case of a German-Slovakian business cooperation. During the study, the research question is divided into three sub-questions: How is the organisational culture constructed? How does organisational structure and practice influence the organisational culture? How do linguistic differences affect the day-to-day business? This objective is investigated through a qualitative study with a participant observation in Slovakia. Then the special role of expatriates in this cooperation is examined through interviews, that try to answer the following sub-questions: Which role do expatriates play related to organisational culture? Which role does expatriate management play? The study revealed that culture in the cooperation is contextual and individually constructed among the involved parties depending on the circumstances. The organisational culture is a construct of local culture, regional history, organisational practice and organisational culture in Germany. It was not based on a cultural line between the nationalities, but on professional identities or rank in internal hierarchy. Here the constructed culture differentiated between management and production level. The German expatriates had an exceptional position. Moreover, the thesis discovered that language barriers covered up fundamental underlying structural problems and had a negative impact on organisational culture. The thereby caused difficulties influenced the flow of information, performance and interpersonal relationships. Additionally, insufficient expatriate management had a negative impact on the established organisational culture. The expatriates shaped the organisational culture with their behaviour. Structural difficulties hindered their adjustment to the setting and performance. Summing up, organisational culture was strongly affected by organisational structure and practice, which reflected in working atmosphere, employee retention and motivation. Language and constructed cultures only reinforced already existing structural weaknesses caused by organisational culture and structure.